Symposium 2: Analysing the pedagogical value of video treatment and text in a digital media application - McCarter, Richard (Proceedings of the International Conference on Networked Learning, 2004)
An Evaluative Case Study of a postgraduate induction programme on CD-Rom containing video examines the pedagogical potential of video and the synergy between video treatment and text. Although the work is still in progress, some useful patterns have emerged. This paper looks at three types of evaluation approaches to collect user feedback on the value of video in order to show that the CD-Rom has made a difference to learning experiences. It also examines the possible relationship between video treatment, text and student motivation and explores the notion that despite the use of a degraded ‘digital’ image, video can be used to generate moods and create a journey of learning for a learning experience and that the experience can influence learning as much as visual richness in educational multimedia.